D-dimer as a surrogate marker for assessment of prognosis in COVID-19 patients: A retrospective study in a tertiary care hospital. - Raman, Ravi Bhushan; Jamal, Iffat; Shuchismita; Choudhary, Manoj Kumar; Choudhary, Vijayanand (Student's Journal of Health Research Africa, 2025)
Background D-dimer has been recognized as a factor that plays an important role in predicting clinical outcomes in COVID-19 patients since the commencement of the pandemic. Objectives- The study was conducted to assess alterations in D-dimer levels in COVID-19 patients. Also, to correlate alterations in levels of D-dimer with the severity of COVID-19 patients clinically, as well as to determine the optimal cut-off value of D-dimer for predicting poor prognosis. Methods The study was retrospective and observational. The study was carried out at the Hematology section (Department of Pathology), Indira Gandhi Institute of Medical Sciences (IGIMS), Patna, Bihar, India. The study included data for a full year, that is, from July 2020 to June 2021. In all, 400 patients were enrolled. Results Elevated D-dimer levels (≥1.5 μg/ml) in COVID-19 patients were significantly associated with older age, higher mortality (45.4% vs. 8.5%), and prolonged hospital stay. D-dimer levels were notably higher in patients aged ≥60 years and in females. The receiver operating characteristic (ROC) curve for admission D-dimer values relative to the clinical outcome of patients provided an area under the curve of 0.818 (95% CI: 0.728–0.886, p < 0.001). The ideal cut-off value of D-dimer for predicting poor clinical outcome was established as 1.5 μg/ml, exhibiting a sensitivity of 70.6% and a specificity of 78.4%. Cox regression identified age and D-dimer as significant predictors of mortality. Among deceased patients, high D-dimer was linked to elevated CRP, indicating severe inflammatory and coagulation responses. Conclusion A straightforward and dependable marker, a strong correlation has been seen to be established between D-dimer and COVID-19. Its application can help direct clinical management, facilitate early risk assessment, and enhance resource allocation. Recommendations Further research is needed with a longitudinal study design and a larger sample to achieve more definitive results.